Elevated plasma trimethyllysine is associated with incident atrial fibrillation - Mads M Svenningsson; Gard FT Svingen; Per M Ueland; Gerhard Sulo; Espen Ø Bjørnestad; Eva R Pedersen; Indu Dhar; Dennis W. Nilsen; Ottar Nygård (American Journal of Preventive Cardiology)
Background/Aim: Trimethyllysine (TML) is a methylated amino acid, which is linked to epigenetic regulation and can serve as a precursor of trimethylamine-N-oxide (TMAO). TMAO is a microbiota-derived metabolite and a potential risk factor of cardiovascular disease. TML has recently been linked to atherosclerosis, acute myocardial infarction and prevalent atrial fibrillation (AF). However, any association between circulating TML and incident AF has not yet been reported and was the aim of the current study in a large community based cohort. Methods: Information regarding AF was obtained by linking patient data to national health registries. Risk associations were explored by logistic regression. Potential improvements in risk reclassification were calculated by the continuous net reclassification index (NRI˃0) and the Receiver Operating Curve Area Under the Curve (ROC-AUC). Results: At baseline 3117 patients were included. During a median (25th-75th percentile) follow-up of 10.8 (9.4 – 11.2) years, 492 patients (15.8 %) developed AF. Higher plasma TML was associated with incident AF per 1 SD log-transformed TML (OR (95 % CI) 1.30 (1.16–1.46) P < 0.01). Further analyses also showed an increase in NRI>0 (95 % CI) of 0.24 (0.14–0.33) P < 0.001 and ROC-AUC (95 % CI) of 0.013 (0.004–0.022) P = 0.006. Conclusion: TML was associated with, and improved risk classification of, new-onset AF in this large cohort of community dwelling adults. Our results motivate further studies on the association between TML and cardiac arrhythmias.